Developing The Software Development Process To Improve The Quality Of Software - Norrgård, Filip (My University, 2010)
The purpose of this thesis is to develop a new software development process in order to improve the quality of the resulting software within an organization specialized in information management. The prior software development process was deemed inefficient at producing high quality software at a reliable rate. This thesis also investigates the terminology to be used in relation to software development activities and the testing activities and terminology. The outcome of this thesis is a new software development process with standardized terminology and documentation. The new software development process was formed on the basis of published prior research in software development processes, software process improvement techniques and software testing. In the new development process, planning of software tests is introduced earlier in the development process to ensure productive testing and consequently more reliable software. Terminologies used in development are clearly defined in order to avoid miscommunication between teams and vendors. The testing process is now in the new model a long running concurrent process that encourages planned and scheduled testing. While the new process can see benefits in a reasonable timeframe, it is necessary that the process is renewed at intervals to adapt to changes in the environment.
Keywords: Software development process; software quality; software testing; software process improvement; fi=Tietotekniikka (KTM)|en=Computer Science|; fi=Tietotekniikan koulutusohjelma (DI)|